Nas águas das tecnologias digitais : os dizeres de um grupo de professores - Pavanelli-Zubler, Élidi Preciliana (2014)
The spread of digital information and communication technologies (TDICs) has caused significant changes to the social relationships and reveal a scenario of challenges for education. Laws and regulations that guide the national education already bring guidelines that include technology in the school curriculum and in teacher education. Nevertheless, we can still observe a certain gap between practices that occur in the classroom and practices in social contexts, demonstrating the relevance of discussing the implications of TDICs in educational contexts. Considering this scenario, this master's research is in the context of continuing education for the use of technologies and aims to analyze the meanings checked in the discourses of teachers on the use of technology also pondering his notes on continuing education for this purpose. This research is grounded in assumptions of interpretive research (BORTONI-RICARDO, 2008; FLICK, 2009), in which teachers from public schools network in the state of Mato Grosso participating in continuing education and using technology with their students were interviewed. The questions shaping this research are: 1) What meanings do teachers attach to the mediation of technology in teaching and learning process? 2) Which meanings does the continuing education offered by CEFAPRO have for my surveyed individuals? With the intent of promoting these reflections, I based my assumptions on Fairclough (2001) to define my position on language and speech; on Sibilia basis (2012), Braga (2010), Lankshear and Knobel (2007) and Buzato (2007, 2010) to discuss the implications of technology in contemporary society with a view to digital literacy and the establishment of a new enunciative ethos and agency of the educator. I also dialogued with the findings of recent searches (ARTUZO, 2011; BRESOLIN, 2011; JESUS, 2007; SILVA, 2014, to name a few) which contributed to mark and consider the analysis and insights on this research. Regarding the training of teachers in relation to the use of technologies, I grounded my studies in Freitas (2009), Gatti and Barretto (2009), Paiva (2013), among others. In the enunciative practices analysis of educators, was perceived justification of the use of technology as a way to illustrate or exemplify a thematic worked and also how to motivate and achieve greater student participation in school activities strategy. It was also evident that teachers emphasize that the school is behind the advancements of society and the perception that changes must happen. Regarding continuing education, the speeched denote that there is a need on the part of some educators, and technical training that is necessary to link theory and practice. It was also evidenced some indications, from educators to the organization of the moments of studies of continuing education. All these findings imply evidence of changes in the ethos of the educator who happens to use the technology as a way to reframe their actions and may be in an unstable moment, immersed in discoveries that lead to several challenges and other postures.